Influence of Cage Shapes on Growth and Production of Silurid Catfish (Mystus cavasius) in Earthen Pond (Annals of Bangladesh Agriculture, 2021)
Influence of three cage shapes viz (i) rectangular ii) square, and (iii) circular on growth and production of Mystus cavasius (local name: gulsha) was studied in earthen pond conditions for a period of 120 days. Each of nine cages, which were made of polyethylene nets, had same internal area (1.80 m3) and stocked with M. cavasius fry at the rate of 300 m-3, following a completely randomized design. Fishes were fed with a commercial floating pellet feed (Mega 002) initially at the rate of 25% of average body weight, with a gradual reduction to 8%. Significantly higher (P0.05) AWG of 10.29 ± 0.10 and 10.43 ± 0.25 g with survival rate of 80 and 83.61%, respectively. A significantly higher (P0.05) in rectangular and square cages, respectively. In case of lengthweight relationship (LWR), the coefficient of determination values (r2) was 0.86, 0.90, and 0.85 in square, circular and rectangular cages, respectively indicating a good linear regression between length and weight in circular cages than square and rectangular cages. Taken together, these results indicate that circular cage is the best for growth, survival and production of gulsha culture in pond condition.Ann. Bangladesh Agric. (2020) 24(2): 59-68